Deep behavioral phenotyping tracks functional recovery following tibia fracture in mice - Jonathan E. Layne; Dustin M. Snapper; Dustin M. Snapper; Molly E. Czachor; Charles Lam; Jacob D. Matityahu; Dane R. G. Lind; Matthieu Huard; Johnny Huard; Kazuhito Morioka; Julian C. Motzkin; Julian C. Motzkin; et al. (Frontiers in Physiology)
IntroductionAn estimated 178 million fractures occur worldwide annually, with lower limb fractures showing high rates of poor healing, often resulting in reduced mobility and chronic pain. Bone healing and the ability to bear weight are closely tied to the mechanical stability of the fracture site. Although fracture stabilization is a well-established factor modulating bone repair, there remains a notable gap in sophisticated non-destructive technologies that can rapidly and objectively quantify functional recovery in preclinical settings. We introduce a novel behavioral phenotyping approach enabling rapid quantification of post-fracture weightbearing and kinematic metrics in freely behaving mice. Our goals were to identify and characterize metrics most indicative of fracture-induced behavioral impairment and to use these metrics to quantify how functional recovery is altered in mice with pin stabilized versus non-stabilized fractures. We also explore sex-specific contributions to recovery.MethodsMale and female C57BL6/J mice received mid-shaft tibial fractures that were either unstabilized or fixed with intramedullary pins; non-fractured mice served as controls. Behavioral recordings were acquired pre-fracture and throughout healing (5–35 days post-fracture). To track mice and analyze changes in paw pressure and kinematics, we performed machine learning-enabled behavioral phenotyping.ResultsOverall, mice with pin-stabilized fractures exhibited less behavioral impairment than mice with unstabilized fractures. Pin stabilization allowed increased weightbearing and produced smaller changes in kinematic metrics. By contrast, we observed only minor sex-specific differences in impairment and recovery following fracture. Our analysis revealed that functional recovery is more complex than individual parameters viewed in isolation, with different parameters identifying distinct recovery timeframes. Therefore, we developed a comprehensive, unified graph theoretic metric encompassing all behavioral parameters. This unified approach confirmed increased severity in unstabilized fractures and identified clear functional recovery windows for both fracture groups.DiscussionThis methodology forms a foundation for future mechanistic experiments focused on biological and mechanical variables influencing functional healing and enables more rapid testing of strategies to accelerate bone healing.